Peran dan Strategi Digitalisasi UMKM Dalam Mendukung Ekonomi Sirkular - Anistia, Sarah; Utami, Rezki Aguswidya; Hasvi, Ismail (Forum Kerjasama Pendidikan Tinggi, 2025)
Digitalization is an important role for MSMEs to adopt sustainable economic practices, such as product lifecycle extension and collaborative consumption. Digitalization has been a catalyst for MSMEs in Jakarta for operational efficiency and adopting the principles of circular economy, a sustainable practice that emphasizes resource efficiency, waste reduction, and use of sustainable materials. Circular economy emphasizes sustainable resource management which is increasingly encouraged by the government to be implemented in various economic sectors. This study aims to identify the influence of digitalization roles and strategies on MSMEs in the Jakarta area in supporting the circular economy. The development of digital technology that can be adopted by the Micro, Small, and Medium Enterprises (MSMEs) sector has increased the number of MSMEs entering the digital ecosystem, especially in urban areas such as Jakarta. This research uses a quantitative method by distributing questionnaires to 100 MSMEs in September 2024 located in the Jakarta City area. Data analysis used regression analysis from SPSS (Statistical Package for the Social Sciences) software. The result of this study obtained a stimulant F value of 416.730> 3.8327 and a significant value of 0.000 <0.05 which indicates that both the role and strategy of digitalization applied to MSMEs has a significant and positive effect on the circular economy in the Jakarta area. This research is expected to enrich the literature on the relationship between digitalization and circular economy, especially in MSMEs in Jakarta.